Indications for selected medical and surgical procedures : a literature review and ratings of appropriateness : carotid endarterectomy - Merrick, Nancy J.; Fink, Arlene; Brook, Robert H. (Robert Henry), 1943-; Kosecoff, Jacqueline B.; Roth, Carol Pindar; McCloskey, Lois.; Keesey, Joan.; Solomon, David H.; Rand Corporation; Commonwealth Fund.; John A. Hartford Foundation; Pew Memorial Trust; et al. (Santa Monica, CA : RAND, 1986)
This report is part of a larger study to determine the extent to which the appropriate use of medical procedures is related to overall rates of use among geographic areas. It is one of six volumes that report the ratings of panels of physicians on the appropriateness of performing each of six procedures for a wide variety of clinically specific indications.The six procedures were coronary angiography, coronary artery bypass graft surgery, cholecystectomy, diagnostic gastrointestinal endoscopy, colonoscopy, and carotid endarterectomy. This volume contains a literature review of carotid endarterectomy, a comprehensive set of indications for performing this procedure, and ratings of the appropriateness for each indication.
"May 1986."
Includes bibliographical references (p. 29-34).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Carotid artery -- Surgery -- United States; Clinical indications; Endarterectomy -- United States; Medical care -- Utilization review -- United States; Surgical indications; Carotid Arteries -- surgery; Endarterectomy -- utilization -- United States; Utilization Review